A Comparative Study on Various Development and Services of Public Libraries In Haryana: Transforming Public Libraries in Rural India (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Public libraries play an important role as parts of thedigital, smart, knowledge and creative infrastructures of these InformationalCities. Libraries have economic value as location factors in the two spaces ofInformational Cities, the physical and the digital. For this reason, we dividedthe library services into two main groups, namely the digital library and thephysical library. The current situation of Indian public libraries has beenviewed by some as follows: the public library system in India is condemned toremain peripheral to the actual information needs of the masses; that it is ina depressed state, and serves as little more than a warehouse of recreationalreading materials, a majority of which are in regional languages. This papersuggests possible remedies on how to transform the situation, and details newtechnological developments which are already showing the potential to changepublic libraries in rural India for the better. The current situation of Indian public libraries has beenviewed by some as follows: the public library system in India is condemned toremain peripheral to the actual information needs of the masses; that it is ina depressed state, and serves as little more than a warehouse of recreationalreading materials, a majority of which are in regional languages. This papersuggests possible remedies on how to transform the situation, and details newtechnological developments which are already showing the potential to changepublic libraries in rural India for the better.